Thermal epimerization of inositol 1,3-benzylidene acetals in the molten state - Gurale, Bharat P.; Krishnaswamy, Shobhana; Vanka, Kumar; Shashidhar, Mysore S. (Tetrahedron, 2011)
1,3-O-Benzylidene-2,4,5,6-tetra-O-substituted-myo-inositol derivatives obtained by the DIBAL-H reduction of the corresponding myo-inositol 1,3,5-orthobenzoate derivatives undergo epimerization at the acetal carbon on heating, in the molten state, just above their melting point. The same epimerization reaction does not proceed either in the crystalline state or in solution. DFT calculations suggest that the epimeric acetal obtained by this thermal process is relatively more stable than the starting acetal. Either of these acetals could not be obtained by the reaction of the corresponding inositol derived diol with benzaldehyde. These observations constitute a novel reaction solely in the molten state, which are rarely encountered in the literature. X-ray crystal structures of the epimeric acetals as well as their radical deoxygenation reaction are also reported. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: cyclitols; Deoxygenation; Epimerization; Melt; Xanthate

Intramolecular cyclization of carbonate and thiocarbonate derivatives of myo-inositol in the solid state: implications for acyl group transfer reactions in molecular crystals - Tamboli, Majid I.; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Krishnaswamy, Shobhana (Chemistry-A European Journal, 2015)
Racemic 4-O-phenoxycarbonyl and 4-O-phenoxythiocarbonyl derivatives of myo-inositol orthoformate undergo thermal intramolecular cyclization in the solid state to yield the corresponding 4,6-bridged carbonates and thiocarbonates, respectively. The thermal cyclization also occurs in the solution and molten states, but less efficiently, suggesting that these cyclization reactions are aided by molecular pre-organization, although not strictly topochemically controlled. Crystal structures of two carbonates and a thiocarbonate clearly revealed that the relative orientation of the electrophile and the nucleophile in the crystal lattice facilitates the intramolecular cyclization reaction and forbids the intermolecular reaction. The correlation observed between the chemical reactivity and the non-covalent interactions in the crystal of the reactants provides a way to estimate the chemical stability of analogous molecules in the solid state.
Keywords: crystal engineering; cyclitols; inositols; nucleophilic substitution; solid-phase synthesis